PENGARUH PELATIHAN PUSH-UP TERHADAP PENINGKATAN KEKUATAN MENARIK DAN MENDORONG OTOT LENGAN - Aryana, I Gede (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This study aimed to determine the affect of training push-up against increased muscle strength of the arm pull and push. This type of research was a quasi-experiment with research design using " The Randomized Pre-Test Post-Test Control Group Design". The samples in this study were male of VIII (eight) grade student of SMP N 1 Mengwi in Academic Year 2012/2013 which amounts to 40 people. The research instruments used to test the strength of arm muscle to pull and push is the expanding dynamometer with reliability was 0.9. The data were analyzed by independent t-test at a significance level of 0.05 with SPSS 16,0. Based on the analysis of research data, by the used of independent t-test for strength of arm muscle pull of data obtained a significance value counting that was smaller than the value of Î± (Sig <0.05) which was equal to 0.044. As for the strength of arm muscle to push resulted significance value that was smaller than the value of Î± (Sig <0.05) that equal to 0.002. Thus the hypothesis of the research training push-up affected to increase the muscle strength of the arm to pull and push were acceptable. From the results of this study, it could concluded that push-up affected the increased muscle strength of the arm to pull and push.